Experiences in sewerage development and management in Malaysia. - Ahmadun, Fakhru'l-Razi; Abang Ali, Abang Abdullah (1983)
There has been a general lack of awareness amongst members of the public as well as goverment to the importance of sewerage development and management. Sewerage problems has in advertently been hidden from public knowledge in the past. This resulted in difficulty in securing sufficient government development funds for sewerage projects. Local authorities are facing a similar problems of shortage of funds and trained manpower to manage existing sewerage systems. However there is now an active effort by engineers in Malaysia to bring sewerage issues to surface. A national policy and strategy for sewerage development and management is currently being discussed.